[Flowers at Reykjavik Park] - Streng, Evelyn Fiedler (1975)
Photograph of flowers at a park in Reykjavik, Iceland. The triangular flower bed is full of red, yellow, purple, and black flowers separated by sprawling lines of white flowers. Green, manicured grass surrounds the flowers and blue river that cuts through the park. A long island formation covered in unkempt grass sits at the center of the river. A large stone statue stands in the field to the left beside lines of rectangular hedges.